Mimachlamys funebris - Dijkstra, Henk H.; Beu, Alan G. (Zenodo, 2018)
Mimachlamys funebris (Reeve, 1853) Figs 86D,G, 88E,G, 92 Pecten funebris Reeve, 1853: sp. 85, pl. 22, fig. 85 (not a junior homonym of Chlamys funebris Lacordaire, 1848, Insecta; ICZN, 1999: 60, Article 57.8); E.A. Smith, 1884: 116; Küster & Kobelt, 1888: 171, pl. 47, fig. 6. Chlamys funebris (Reeve).–Wells & Bryce, 1988: 160, fig. 588; Wells, Slack-Smith & Bryce, 2000: 42. Chlamys (Mimachlamys) funebris (Reeve).– Rombouts, 1991: 28, pl. 11, figs 2–2a; Lamprell & Whitehead, 1992: [22], pl. 9, fig. 54. Mimachlamys funebris (Reeve).–Beu & Darragh, 2001: 181, fig. 47E; Slack-Smith & Bryce, 2004: 237; Raines & Poppe, 2006: 270, 273, upper figs; pl. 217, figs 1–5; Huber, 2010: 210. Type data . Type material not traced in NHMUK. Type locality: Bathurst Island, Western Australia. The illustrated articulated specimen, from WA, Broome, Entrance Point (WAM S55490; Figs 86D, G, 88E, G) is here designated the neotype of Pecten funebris Reeve, 1853. Additional material examined . —AUSTRALIA: WESTERN AUSTRALIA : Cardabia, S of Point Cloates, 23°06'S 113°48'E, dead (1 v, C.375604); Point Cloates, 22°43'S 113°40'E, dead (1 v, C.375605); Exmouth Gulf, 17 ml S of Exmouth townside, 22°13'S 114°06'E, dead (1 v, C.093621; 1 v, C.375607); North West Cape, Lighthouse Beach, 21°49'S 114°11'E, dead (2 v, C.100740); Turtle Beach, W side of North West Cape, 21°48'S 114°10'E, dead (4 v, C.375606); S Muiron Island, off SW coast, 21°41.55'S 114°18.17'E, dead, 19–20 m (1 v, WAM S12834); S Muiron Island, off NE coast, 21°40.46'S 114°20.91'E, dead, 3–5 m (1 v, WAM S12785; 1 v, WAM S12836); S Muiron Island, off North West Point, 21°39.45'S 114°20.22'E, dead, 11–13 m (1 v, WAM S12835); Onslow Beach, 21°38'S 115°07'E, dead (1 v,C.119519); Onslow area, 21°38'S 115°07'E, dead (2 v, C.375608); Onslow, W side of Peak Island, 21°36'S 114°30'E, alive, 18 m (4 pr + 2 v, WAM); Bundegi Reef, 21°51'S 114°10'E, dead (1 v, WAM); Exmouth, Bundegi Reef, 21°15'E 114°11'E, alive (3 pr, C.344047); Exmouth, Bundegi Reef, 21°51'S 114°11'E, alive, 0–3 m (1 pr, C.344046); 40 ml S of Dampier, 21°0'S 116°06'E, dead (1 v, C.375609); Passage Island, Sholl Island, NE side, 20°57'S 113°53'E, dead, intertidal (1 pr, WAM); between Cape Dupuy and Cape Malouet, Barrow Island, 20°40'-42'S 115°25'E, dead (1 v, WAM); Montebello Islands, Buttercup Island, 20°29.16'S 115°32.04'E, dead, intertidal (1 pr, WAM); Montebello Islands, Stephenson Channel near S end of Hermite Island, 20°28'21"S 115°32'27"E, dead, 4 m (2 v, WAM S12838);Montebello Islands, E side of Trimouille Island,dead (3 v, WAM);Montebello Islands,S of Gannet Island to E of Delta Island,stn MB#12, 20°27'S 115°33.59'E, dead, 4–6 m (1 v, WAM S12974); Montebello Islands, 20°26'S 115°32'E, alive (1 pr, C.049666;1 pr,C.132070);Montebello Islands, near rock islands,SW end of Bluebell Island, 20°23'30"S 115°31'04"E,dead, 0–9 m (1 v, WAM S12839);Montebello Islands, 20°21'16"S 115°30'53"E, inside reef of North-West Island, dead, 3–4 m (1 v, WAM S12837); Dampier Archipelago, Rosemary Island, 20°29'S 116°35'E,alive (2 pr, WAM);DampierArchipelago,NE corner of Delambre Island,approx. 20°26'S 117°10'E, alive (1 pr, WAM); Dampier Archipelago, N end of Flying Foam Passage, 20°28'S 116°50'E, alive (1 pr, WAM); Port Hedland, 20°18'S 118°35'E,alive (1 pr, WAM); Port Hedland, 20°18'S 118°35'E, alive (1 pr, C.097536; 1 pr,C.119518);Lagrange, 18°37'S 121°43'E, alive (1 pr, WAM);Lagrange Bay, 18°38'S 121°42'E, alive (2 pr,C.103817); c. 230 ml W of Roebuck Bay, 18°30'S 118°03'E, dead, 238 m (1 v, C.165163);Broome, 17°58'S 122°14'E,alive (3 pr, WAM);Broome, Entrance Point, 18°01'S 122°12'E,alive, intertidal (4 pr, WAM);Broome, Entrance Point, 18°01'S 122°12'E,dead (3 v,C.119521; 2 pr, C.121369); Broome, Roebuck Bay, 18°0'S 122°15'E, alive (1 pr, C.097537; 1 pr, C.132071; 3 pr,C.344037); Gantheaume Point, W of Broome, 17°59'S 122°11'E, dead (1 pr, C.057197);Black Ledge,Roebuck Bay, S of Broome, 17°59'S 122°17'E, dead (4 pr,C.303776);Broome, 17°58'S 122°14'E, alive 0–16 m (1 v, C.075235; 3 v, C.375613; 1 pr,C.375612);Broome, Cable Beach, 17°56'S 122°12'E,dead (5 v,C.375610);Rowley Shoals, Imperieuse Reef, 17°31'S 118°56'E, dead (2 v, WAM);Kimberley,Beagle Bay, 16°56'S 122°32'E, dead (many v, C.119520; 10 v, C.119522); Kimberley, Beagle Bay, 16°52'S 122°32'E, dead, 9 m (1 pr, WAM); King Sound, 16°50'S 123°30'E, alive (2 pr, C.097538); Kimberley, Sunday Island, Derby, 16°25'S 123°11'E, dead (1 pr + 1 v, WAM); Kimberley, Sunday Island, S side, 16°26'S 123°09'E, dead, 23 m (1 v, WAM); Cape Leveque, 16°24'S 122°55'E,alive (2 v, C.160997; 1 pr, C.061584; 1 v, C.375614; 1 pr, C.095818; 1 v, C.375615). Description . Shell up to c. 70 mm high, most specimens smaller, to c. 50 mm; dorsoventrally elongate, weakly inflated, almost equally convex, equivalve, almost equilateral, anterior auricles much larger and longer than posterior ones, umbonal angle c. 85–90°; most specimens brownish, a few orange, red or yellow; mottled in juvenile stage, more uniform in adults. Both valves sculptured with c. 20–25 evenly spaced, squamose radial plicae; a narrow secondary riblet present on each side of each plica, commencing on central part of disc of mature shells. Anterior auricle of left valve with c. 10 squamose radial riblets, weaker and fewer (c. 6) on posterior auricle; anterior auricle of right valve with 4–5 prominent radial riblets, much weaker on posterior. Dorsal margin somewhat declined on posterior auricle. Byssal notch deep, byssal fasciole rather broad. Functional ctenolium well-developed, with 4–6 teeth. Interior radially furrowed, internal rib carinae prominent in narrow zone around ventral margin. Resilial and dorsal teeth prominent. Dimensions . Illustrated specimen: WA, Broome, Entrance Point (WAM S55490): H 48.4, L 42.4 mm. Habitat . Living in the upper littoral zone, byssally attached to undersides of rock slabs on hard reef at minus tide levels only. Usually slabs are in shallow pools or in almost dried out gutters (pers. comm. H. Morrison, 2000). Distribution . Mainly along the shores of northern Western Australia, from Shark Bay to the Kimberley. Present specimens alive in the intertidal zone to 18 m. Remarks . This species easily could be confused in the juvenile stage with Mimachlamys punctata (Gmelin, 1791), a common species from the tropical Southwest Pacific, also occurring in the tropical region of Australia, although more offshore than M. funebris in Western Australia. The two species can be distinguished by size, sculpture and colour (Table 7). : Published as part of Dijkstra, Henk H. & Beu, Alan G., 2018, Living Scallops of Australia and Adjacent Waters (Mollusca: Bivalvia: Pectinoidea: Propeamussiidae, Cyclochlamydidae and Pectinidae), pp. 113-330 in Records of the Australian Museum (Rec. Aust. Mus.) (Rec. Aust. Mus.) 70 (2) on page 282, DOI: 10.3853/j.2201-4349.70.2018.1670, http://zenodo.org/record/5299017 : {"references": ["Lacordaire, J. T. 1848. Monographie des coleopteres subpentameres de la famille des phytophages. Tome second. Memoires de la Societe Royale des Sciences de Liege 5: i - vi, 1 - 890.", "Smith, E. A. 1884. Mollusca. In Report on the Zoological Collections Made in the Indo-Pacific Ocean During the Voyage of the H. M. S. \" Alert \" 1881 - 2, pp. 34 - 116, 487 - 508. London: Trustees of the British Museum.", "Rombouts, A. 1991. Guidebook to Pecten Shells. Recent Pectinidae and Propeamussiidae of the World [edited and revised by H. E. Coomans, H. H. Dijkstra, R. G. Moolenbeek and P. L. van Pel]. Oegstgeest: Universal Book Services."]}